1983
DOI: 10.1152/jappl.1983.54.4.934
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of airway tone during exercise in patients with asthma

Abstract: In 10 nonasthmatic subjects and 11 patients with asthma, we measured pulmonary resistance (RL), functional residual capacity (FRC), and specific conductance (sGaw) before, during, and after submaximal treadmill exercise. Nonasthmatic subjects did not change RL, FRC, or sGaw from base-line resting values during or after exercise. In patients with asthma, RL decreased significantly during exercise, both when exercise was begun from the control resting state and from conditions of elevated RL after a preceding pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 0 publications
3
45
0
Order By: Relevance
“…Airway resistance rose considerably in response to methacholine administration when tidal volume was zero, whereas the bronchoconstrictor response was progressively attenuated when the same methacholine dose was given during mechanical ventilation with higher and higher tidal volumes; indeed, bronchoconstriction was prevented essentially completely by mechanical ventilation with large (20 ml/kg) tidal volumes. Hyperpnea similarly suppresses bronchoconstriction in other animals and in humans (7)(8)(9)(10), and accounts for the delayed onset of bronchoconstriction induced in subjects with asthma by exercise (which provokes hyperpnea) or by eucapnic voluntary hyperventilation of dry air, until after cessation of exercise or hyperpnea. Thus, even in asthma, deep breathing functionally antagonizes bronchoconstriction, though studies (11)(12)(13)(14)(15) suggest that the degree to which breathing antagonizes bronchoconstriction may be abnormally reduced in subjects with asthma.…”
Section: Smooth Muscle Contraction and Airway Constrictionmentioning
confidence: 96%
“…Airway resistance rose considerably in response to methacholine administration when tidal volume was zero, whereas the bronchoconstrictor response was progressively attenuated when the same methacholine dose was given during mechanical ventilation with higher and higher tidal volumes; indeed, bronchoconstriction was prevented essentially completely by mechanical ventilation with large (20 ml/kg) tidal volumes. Hyperpnea similarly suppresses bronchoconstriction in other animals and in humans (7)(8)(9)(10), and accounts for the delayed onset of bronchoconstriction induced in subjects with asthma by exercise (which provokes hyperpnea) or by eucapnic voluntary hyperventilation of dry air, until after cessation of exercise or hyperpnea. Thus, even in asthma, deep breathing functionally antagonizes bronchoconstriction, though studies (11)(12)(13)(14)(15) suggest that the degree to which breathing antagonizes bronchoconstriction may be abnormally reduced in subjects with asthma.…”
Section: Smooth Muscle Contraction and Airway Constrictionmentioning
confidence: 96%
“…Shen and coworkers demonstrated in ventilated rabbits that breathing reduced methacholine-elicited airway resistance in a tidal volume-dependent manner (5). In normal individuals who demonstrated increased airway resistance to inhaled methacholine, the degree of bronchoconstriction could be reversed again by normal, tidal breathing (6,7) or by taking a single deep inspiration (8)(9)(10). This airway dilation with deep inspiration also was demonstrated directly by looking at computed tomography (CT) scans of normal volunteers (8).…”
mentioning
confidence: 95%
“…actin filament dynamics; force oscillations; isotonic contractions; hysteresivity A NUMBER OF PREVIOUS STUDIES in animals (22,24,25,27) and humans (7,29) have demonstrated that tidal breathing per se reduces airway constriction during contractile stimulation, and deep breathing does so more effectively. Even a single deep inspiration can substantially reverse experimentally induced bronchoconstriction in normal individuals (1, 4, 11).…”
mentioning
confidence: 99%